2010
DOI: 10.1063/1.3485084
|View full text |Cite
|
Sign up to set email alerts
|

Visible iridescence from self-assembled periodic rippling in vertically aligned carbon nanotube forests

Abstract: We observe iridescence in the form of spectrally dispersed white light reflected from the structured sidewalls of vertically aligned carbon nanotube forests. The iridescence is a result of diffraction from a self-assembled periodic rippling pattern on the forest sidewalls that acts as a reflection grating. We measure the grating spacing via white light and laser diffraction experiments and see good agreement with the spacing of the rippling pattern as measured via scanning electron microscopy. The periodic rip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…The observed colour changes from red to blue (a-j) as the angle of incidence is swept across the sample in 4°i ntervals. Based on the diffraction data the grating spacing is 330 ± 140 nm, which agrees with the 470 ± 10 nm measured by SEM [20].…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The observed colour changes from red to blue (a-j) as the angle of incidence is swept across the sample in 4°i ntervals. Based on the diffraction data the grating spacing is 330 ± 140 nm, which agrees with the 470 ± 10 nm measured by SEM [20].…”
Section: Resultssupporting
confidence: 75%
“…Previously, we showed that rippled forests, such as those in the present report, can be observed optically via diffraction because they behave as gratings [20]. This effect allows their periodicity to be directly calculated from the simple grating equation, and shows that the ripples are very consistent over significant areas, for if they were not, clear diffraction patterns, such as those observed here, would not be seen.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…At lower temperatures, morphologies become even more complicated, with self-delamination common in the range 730°C and 760°C (figure 2c) and even cracking and "exploding" at lower temperatures (figure 2d). In the intermediate range of temperatures (~730°C to ~830°C), the forests reproducibly show periodic ripples on their outer surface of wavelength ~1 µm, extending over a large range (19,20). The ripples are so regular, over much of the forest height, that one can even obtain optical diffraction patterns from them.…”
Section: Resultsmentioning
confidence: 99%
“…Kempa et al 9 fabricated honeycomb-structure arrays of vertically aligned CNTs and observed strong colorful diffraction from the nanotubes because of their high metallicity (i.e., low dielectric loss). Vinten et al 10 reported visible iridescence from the sidewalls of CNT forests due to the ripples present on the sidewalls. Shoji et al 11 developed an optical polarizer made of aligned single-walled CNTs.…”
mentioning
confidence: 99%